Lafizat Albahr Fi Alquran Alkrym - Tafsir Waejaz- - Saed , Najlaa; Jamil, Razan (Islamic Sciences Journal, 2023)
ABSTRACT The Book of Allah is characterized by the fact that it addresses the mind and the soul together, It explains scientific facts and reinforcing them with the main goal of proving the oneness of Allah to those who susbect this. The scholars are different in the definition of the sea each according to its approach and purpose. In the current research we collected definitions and verses that include the word sea and its derivatives, and we were exposed to the interpretation of selected verses with varying meanings according to the Qur'anic context, as we addressed the scientific miracles of certain verses containing the word, proving scientific facts discovered on the water of the sea later, indicates the oneness of the Creator and the greatest of his making.